Influence of Elaeagnus angustifolia flour on the organoleptic and physicochemical characteristics of bread (LAVASH) - Nezamdoost-sani, Narmin; Asghari-jafarabadi, Mohammad; Mohtadinia, Javad (Progress in Nutrition, 2018)
In this study the influence of Elaeagnus angustifolia flour including all parts of the fruit (pulp, skin and core) added at different levels 2.5, 5, 7.5 and 10% on organoleptic and physicochemical characteristics of functional bread (LAVASH) were investigated. The moisture and protein content of treated bread decreased while ash, acidity, glucose, fructose, total sugar, fat content and water activity had been increased compared to control. This flour increased the sweetness of treated samples. Due to technological problems addition of E. angustifolia flour up to 7.5% was more acceptable. Organoleptic properties of treated types were approved by the evaluators.